2021
DOI: 10.5334/ijic.5605
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Early Impacts of an Integrated Care Pilot Program in China: Case Study of County-level Integrated Health Organizations in Zhejiang Province

Abstract: Background: One of the most noticeable integrated care-related policies in China is the growth and proliferation of County-level Integrated Health Organizations (CIHOs), which take over a set of primary healthcare institutions to form an integrated delivery network in order to achieve an ordered hierarchical delivery system by strengthening primary care.Objectives: This paper presents emerging findings from an ongoing evaluation of the early impacts of the demonstrator site, Deqing CIHO, in Zhejiang Province, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This demonstrated that strategies taken in the hospital group did not bring coordinated care to patients. 32 Several studies implied potential reasons for small or no differences in patients’ perception of integrated care. 33 - 35 Firstly, the inter-institutional coordination of health resources in the hospital group were not implemented well.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that strategies taken in the hospital group did not bring coordinated care to patients. 32 Several studies implied potential reasons for small or no differences in patients’ perception of integrated care. 33 - 35 Firstly, the inter-institutional coordination of health resources in the hospital group were not implemented well.…”
Section: Discussionmentioning
confidence: 99%
“…In order to mitigate the biases that may afect outpatient and inpatient visits of THCs other than remoteness of location, we controlled for a range of features of THCs, such as number of physicians, number of served populations, percentage of served populations aged 65 and above, government subsidies as a percentage of revenue [4], and type of THCs. Moreover, considering the possible crowding-out efect of local county hospitals on THCs [23][24][25], we included the number of available bed days in local county hospitals and county categories in regression models. For better presentation, we summarized the details about the values and attributes of the abovementioned variables in Table 1.…”
Section: Variable Measuresmentioning
confidence: 99%